Revitalising reflective practice in pre-service teacher education: developing and practicing an effective framework. Issue 3 (4th May 2021) - Roberts, Pauline; Barblett, Lennie; Boylan, Fiona; Knaus, Marianne
ABSTRACT: Reflective practice plays a significant role in effective teaching. However, for pre-service teachers (PSTs), it can be a difficult process to not only think reflectively but to understand its importance in their teaching practice. This research focused on the development of a framework for written reflective practice embedded within professional experience (PEx) units. In tutorials, PSTs were provided with video technology to film themselves performing teaching tasks. A reflective framework provided a structure to assist in reflecting on the teaching task. Dialogical teaching and coaching by tutors as well as peer discussion scaffolded the reflective process. At the end of the semester, PSTs and tutors were invited to complete a survey on the reflective processes they had used. This paper focuses on the development of the reflective framework and the feedback received on the use of the framework as a reflective tool. The findings reveal that the PSTs and most tutors found the format useful in structuring reflective practice. The framework and its repeated use over time has potential to build professional knowledge and skills and sustain ongoing reflective practice into the PSTs professional careers.